A-31 Association Between Cognitive Activity and Recovery Outcomes in College Students Following Concussion. (18th June 2020) - Petit, K M; Zynda, A J; Anderson, M; Tomczyk, C P; Covassin, T
Abstract: Objective: To evaluate the relationship between self-reported cognitive activity and recovery outcomes (symptom reporting, recovery time) in college students following concussion. Method: Cognitive activity was defined as self-reported minutes spent in class and studying during the first 5 days following concussion. Self-reported symptoms were reported at day 5 post-injury using the Post-Concussion Symptom Scale (PCSS). The PCSS evaluates 22 symptoms on a 7-point Likert Scale from 0 (none) to 6 (severe). Recovery time was defined as total days from injury to unrestricted medical clearance. Separate Spearman's rank correlations assessed the relationship between total cognitive activity (minutes in class and studying) and recovery outcomes (symptom total (22), symptom severity (132), and recovery time). Alpha level set a priori at 0.05. Results: Twenty-one participants (14 female, 7 male, 19.5 ± 1.3 years) averaged a total of 653[IQR = 348] minutes of cognitive activity during the first 5 days after concussion (334[IQR = 149] minutes in class, 273[IQR = 313] minutes studying). Five days after injury, participants self-reported 3[IQR = 8] total symptoms yielding a severity of 4[IQR = 12]. Participants took 15 [IQR = 8] days to reach unrestricted medical clearance. No associations were found between total cognitive load and any post-concussion recovery outcomes (symptom total: Rs = −.299, p = .19; symptom severity: Rs = −.230, p = .32; recovery time: Rs = −.041, p = .86). Conclusions: Preliminary analyses suggest that concussed college students can be encouraged to gradually return to normal levels of cognitive activity, as it may not be associated with future symptom reporting or recovery time. Future research is needed to assess specific cognitive activities immediately influence on post-concussion symptom reporting.